Influence of low frequency magnetic field used in magnetotherapy on interleukin 6 (IL-6) contents in rat heart and brain - Elżbieta Ciejka; Beata Skibska; Anna Gorąca (Nofer Institute of Occupational Medicine, 2017)
Background: The human population is exposed ever more frequently to magnetic fields (MF). This is due to both technological progress and development of the economy as well as to advances made in medical science. That is why the thorough understanding and systematized knowledge about mechanisms by which MF exerts its effects on living organisms play such an important role. In this context the health of MF-exposed people is the subject of particular concern. The aim of the study was to evaluate the effect of extremely low frequency magnetic field (ELFMF) used in magnetotherapy on the concentration of interleukin 6 (IL-6) in rat heart and brain. Material and Methods: The male rats were randomly divided into 3 experimental groups: group I - control, without contact with magnetic field; group II − exposed to bipolar, rectangular magnetic field 40 Hz, induction "peak-to-peak" 7 mT 30 min/day for 2 weeks; and group III − exposed to bipolar, rectangular magnetic field 40 Hz, 7 mT 60 min/day for 2 weeks. Concentration of IL-6 in the heart and brain of animals was measured after MF exposure. Results: Exposure to ELFMF: 40 Hz, induction "peak-to-peak" 7 mT 30 min/day for 2 weeks caused a significant IL-6 increase in rat hearts compared to the control group (p < 0.05) and a non-significant IL-6 decrease in rat brain. The magnetic field applied for 60 min resulted in non-significant IL-6 increase in rat hearts compared to the control group and significant IL-6 decrease in rat brain (p < 0.05). Conclusions: The influence of magnetic field on inflammation in the body varies depending on the MF parameters and the affected tissues or cells. Med Pr 2017;68(4):517-523